Intravenous acetaminophen with morphine versus intravenous morphine alone for acute pain in the emergency room: protocol for a multicenter, randomized, placebo-controlled, double-blinded study (ADAMOPA) - Cattin, Guillaume; Jenvrin, Joel; Hardouin, Jean Benoit; Longo, Céline; Montassier, Emmanuel (Current controlled trials in cardiovascular medicine, 2022)
Background In emergency medicine, pain is a frequent reason for consultation. However, there is a great variation in its management which is often insufficient. The use intravenous morphine alone or multimodal analgesia with paracetamol is recommended for severe pain. But robust data are lacking to justify the association of paracetamol with morphine versus morphine alone for pain management in the emergency room (ER). The aim of our study is therefore to assess if in patients with acute pain of moderate to severe intensity with a numerical verbal scale (NVS) ≥5 in the ER, the intravenous administration of morphine alone is not inferior to the administration of intravenous morphine combined with paracetamol at 30 min from the first administration of the study drug. Methods ADAMOPA is a prospective, non-inferiority, multicenter, placebo-controlled, parallel-group, randomized (1:1), double-blind trial. Subjects will be enrolled in the ER if they experience moderate to severe, acute, non-traumatic, and traumatic pain, defined as an NVS ≥5. The primary endpoint will be the between-group difference in mean change in NVS pain scores among patients receiving the combination of intravenous morphine plus paracetamol or intravenous morphine given alone, measured from the time before administration of the study medication to 30 min later. Discussion This trial will determine the clinical utility of the association of paracetamol with morphine for pain management in the emergency room. The ADAMOPA trial will be conducted in accordance with the International Council on Harmonization Good Clinical Practices. Trial registration EudraCT number: 2019-002149-39. ClinicalTrials.gov identifier: NCT04148495. Date of trial registration: November 1, 2019.